PENGEMBANGAN PUZZLE SEGITIGA UNTUK MEMFASILITASI KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Cantika Dhany Rahmania, Sekar; Saputro, Bagus Ardi; Januar Saputra, Henry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was developed to create a Triangle Geometry Puzzle learning media to support the mathematical representation abilities of fourth-grade elementary school students, especially in recognizing, analyzing, composing, and breaking down various types of triangles according to Phase B Learning Outcomes of the Independent Curriculum. From the findings of interviews with teachers of SDN 3 Tlogotirto which showed a lack of concrete media in mathematics lessons, so that students were less enthusiastic, tended to be passive especially at the back of the class, and had difficulty representing triangles concretely because they depended on KUMER/LKS books and simple lecture/discussion methods. The main objectives included an assessment of the feasibility and description of the practicality of the media. The ADDIE model Research and Development approach was applied through the stages of needs/curriculum/material analysis, design using GeoGebra/CorelDRAW, development of a fourteen by fourteen centimeter black-and-white acrylic puzzle with seven types of triangles plus a QR code containing an explanation of the triangle material including properties/characteristics/types, explanatory animated videos and Wordwall quizzes. Based on the analysis, an average percentage was obtained with very practical criteria, indicating that the puzzle media meets the needs and characteristics of elementary school students. The black and white triangle puzzle display is accompanied by various concrete shapes of triangle types so that it attracts attention and increases learning focus.